PHYSICAL CHARACTERISTICS, DIGESTIBILITY, AND RUMEN FERMENTATION PRODUCTS IN-VITRO OF RICE STRAW SILAGE USING LIGNOCELLULOLYTIC BACTERIA BIOCATALYS - I M. D. Y., Putra; Mudita, I M.; Sutama, I N. S. (Jurnal Peternakan Tropika; Vol 8 No 3 (2020): Vol. 8 No. 3 Tahun 2020; September - December, 2020)
The study airms to determine the physical characteristics, digestibility, rumen fermentation products in-vitro of rice straw silage using lignocellulolytic bacteria biocatalys. This study has conducted at the Sesetan Farm and the Laboratory of Nutrition and Animal Feed, Faculty of Animal Husbandry, Udayana University from January to March 2020. The design used has a completetly randomized design (CRD) consisting of 6 treatments namely the silage of rice straw silage without lignocellulolytic bacteria biocatalys as a control (JP0), using a bacteria biocatalys Bacillus substilis BR 4 LG (JP1), using a bacteria biocatalys Bacillus substilis BR 2 CL (JP2), using a bacteria biocatalyst Aneurinibacillus sp. BT 4 LS (JP3), using a bacteria biocatalys Bacillus sp. BT 3 CL (JP4), and using a bacteria biocatalys Bacillus sp. BT 8 XY (JP5) and each treatment has 3 replications. The observed variables were physical characteristics, digestibility and rumen fermentation products. Collected data were analyzed by analysis of variance. The results showed that quantitative JP2 treatment has the highest density (P>0.05) of 0,166 g/ml. Quantitative JP4 treatment has the highest percentage of water regain capacity (P>0.05) of 369,55% and resulted the highest percentage of water solubility and N-NH 3 (P<0.05) of 85,75% and 12,39 mM, respectively. P1 treatment resulted in the highest percentage of dry matter and organic matter digestion (P<0.05) of 51,55% and 54,21%, respectively. JP5 treatment resulted the highest VFA Total (P<0.05) of 180,52 mM. Based on these result can be concluded that the use of lignocellulolytic bacterial biocatalysts can improve physical characteristics, especially water solubility and increase digestion and rumen fermentation products in-vitro of rice straw silage. The best bacterial biocatalyst in this study has Bacillus substilis BR 4 LG resulted the highest of dry matter and organic matter digestion and Bacillus sp. BT 3 CL resulted the highest water solubility and N-NH 3 . Keywords:    Lignocellulolytic bacterial biocatalys, In-vitro, Rice straw, Silage